Baseline self-efficacy predicts subsequent engagement behavior in an online physical activity intervention - Lee, Seungmin; Myers, Nicholas D.; Bateman, André G.; Prilleltensky, Isaac; McMahon, Adam; Brincks, Ahnalee M. (Frontiers in Sports and Active Living, 2024)
Background: The purported benefits of online physical activity interventions, in terms of reduced costs, high reach, and easy access, may not be fully realized if participants do not engage with the programs. However, there is a lack of research on modifiable predictors (e.g., beliefs) of engagement with online physical activity interventions. The objective of this brief report was to investigate if self-efficacy to engage at baseline predicted subsequent engagement behavior in an online physical activity intervention at post-baseline. Methods: Data (N = 331) from the 2018 Fun For Wellness effectiveness trial (ClinicalTrials.gov, identifier: NCT03194854) were analyzed in this brief report. Multiple logistic regression was fit in Mplus 8 using maximum-likelihood estimation. Results: There was evidence that self-efficacy to engage beliefs at baseline positively predicted subsequent engagement behavior in the Fun For Wellness intervention at 30 days post-baseline. Conclusions: Some recommendations to increase self-efficacy to engage in future online physical activity intervention studies were provided consistent with self-efficacy theory.